Description of the lucky Cophyla (Microhylidae, Cophylinae), a new arboreal frog from Marojejy National Park in north-eastern Madagascar - Rakotoarison, Andolalao; Scherz, Mark D.; Bletz, Molly C.; Razafindraibe, Jary H.; Glaw, Frank; Vences, Miguel (Zootaxa, 2019)
We describe a new species of arboreal microhylid frog from northern Madagascar. The new species is assigned to the genus Cophyla based on molecular phylogeny and morphological similarities to other species of this genus. Molecular phylogenetic analysis resolved Cophyla fortuna sp. nov. as closely related to C. noromalalae. However, the two species were reciprocally monophyletic both in a tree reconstructed from a combination of mitochondrial genes, and in a tree based on the nuclear RAG-1 gene. The new species, previously identified as candidate species Cophyla sp. Ca4, occurs in lowland bamboo forests around the Marojejy Massif in northeastern Madagascar. It differs from the allopatric C. noromalalae, so far only known from the Montagne d’Ambre Massif in northern Madagascar, by slightly smaller body size and shorter duration and higher spectral frequency of advertisement calls. Several additional genetically divergent mitochondrial lineages of Cophyla, related to the C. fortuna/noromalalae complex and to C. phyllodactyla, occur in intervening areas between Montagne d’Ambre and Marojejy, and their status requires further study.